2002
DOI: 10.1097/00000433-200206000-00016
|View full text |Cite
|
Sign up to set email alerts
|

A New Improved Method for Extraction of DNA From Teeth for the Analysis of Hypervariable Loci

Abstract: A new method for better recovery of DNA suitable for amplification of hypervariable loci from fragments of teeth, consisting of two steps-scraping and aspiration, and extensive decalcification-is reported. Higher yields of high molecular weight DNA were obtained from the root, pulp, and crown of all kinds of 120 teeth, irrespective of gender, age, and source of teeth. HLA DQA1, 5 poly markers (LDLR, GYPA, HBGG, D7S8, and Gc), and other 12 short tandem repeat loci (HPRTB, F13B, LPL, D13S317, D7S820, D5S818, D21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…The results of our study are similar to those of Trivedi et al [18] who proposed a three-stage scraping and aspiration technique to access dental DNA. In contrast, in the literature some studies report that the crushing preparation gives better results than the trepanation method [19].…”
Section: Depending On the Methods Selectedsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of our study are similar to those of Trivedi et al [18] who proposed a three-stage scraping and aspiration technique to access dental DNA. In contrast, in the literature some studies report that the crushing preparation gives better results than the trepanation method [19].…”
Section: Depending On the Methods Selectedsupporting
confidence: 90%
“…In adults, the average pulp volume is 0.020 ml [20]. Third molar pulp volumes range from 0.023 ml for the maxillary teeth to 0.031 ml for mandibular teeth [18].…”
Section: Depending On the Teeth Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by Miloš et al [10] and Primorac [11] that respectively reported a 82.7% and a 85% success rate obtained by the destruction of the tooth (crushing/ grinding technique). Trivedi et al [12] used an endodontic technique to extract pulp and found a variable success percentage from 60% to 100%. We did not find any previous studies that addressed the possibility of multiple DNA extraction at different times from the same dental element.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling of the tooth for DNA extraction Various methods have been reported regarding the extraction of DNA from the tooth which includes sectioning of teeth horizontally at the cemento-enamel junction or vertically up to root tip, scraping and aspiration. 33,34 In a modified horizontal sectioning procedure, the tooth is circumferentially scored 1 mm below the cemento-enamel junction with a long-shanked round bur leaving a 2e3 mm wide isthmus of intact tooth structure on the facial surface. The crown is then manually separated from the root.…”
Section: Teeth and Dna Analysismentioning
confidence: 99%